2015
DOI: 10.15282/ijame.11.2015.17.0198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Time on Microstructure and Mechanical Properties of Aa6061 Friction Stir Welding Joints

Abstract: This study was to determine the influences of post-weld heat treatment (PWHT) on the tensile and microstructure properties of friction stir-welded AA6061 aluminum alloy joints. Friction stir welding (FSW) of aluminum alloys has the potential to retain good mechanical and metallurgical properties. 3 mm plate AA6061 aluminum alloy was used to fabricate the joints. Solution heat treatment, quenching plus an artificial aging treatment with different times of aging were adopted. The fracture surface of the welded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…A simple artificial aging treatment was able to enhance the tensile properties of his specimen which is 3mm plate aluminium alloy 6061. From the result, it shows an increment of tensile strength from 0.3% to 4.7% when the time of aging was increased [31]. Another aging condition which is the natural aging is a process of aging in which the specimens were put through in a room temperature for a period of time [23].…”
Section: Agingmentioning
confidence: 97%
“…A simple artificial aging treatment was able to enhance the tensile properties of his specimen which is 3mm plate aluminium alloy 6061. From the result, it shows an increment of tensile strength from 0.3% to 4.7% when the time of aging was increased [31]. Another aging condition which is the natural aging is a process of aging in which the specimens were put through in a room temperature for a period of time [23].…”
Section: Agingmentioning
confidence: 97%
“…This layer assists in the welding process because Zn has good metallurgical compatibility with both aluminium and steel [15,20,27,28]. Other than that, many researchers have also pointed out that the base and filler metal elements have a significant effect on the joint strength [29][30][31]. In this study, a detailed investigation on aluminium-galvanized iron dissimilar welding is conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Each zone experiences dissimilar plastic deformations, leading to different shapes of microstructure. In order to produce a sound welding joint, welding parameters such as rotational speed, transverse speed, and position of the metals either on the advancing or retreating side should be considered during the FSW process [13][14][15]. Research by Dawood et al [16] found that reduction in surface roughness reduces friction and narrows down the HAZ at the welding joint.…”
Section: Introductionmentioning
confidence: 99%